2016
DOI: 10.3758/s13414-016-1195-3
|View full text |Cite
|
Sign up to set email alerts
|

How does cognitive load influence speech perception? An encoding hypothesis

Abstract: Two experiments investigated the conditions under which cognitive load exerts an effect on the acuity of speech perception. These experiments extend earlier research by using a different speech perception task (four-interval oddity task) and by implementing cognitive load through a task often thought to be modular, namely, face processing. In the cognitive-load conditions, participants were required to remember two faces presented before the speech stimuli. In Experiment 1, performance in the speech-perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Our results argue for a temporal ordering of effects such that acoustic context effects precede any modulating effects of cognitive load. This proposal is in line with a recent study by Mitterer and Mattys (2016). They argue that cognitive load does not necessarily or solely reduce the fidelity of early perceptual processes.…”
Section: Discussionsupporting
confidence: 91%
“…Our results argue for a temporal ordering of effects such that acoustic context effects precede any modulating effects of cognitive load. This proposal is in line with a recent study by Mitterer and Mattys (2016). They argue that cognitive load does not necessarily or solely reduce the fidelity of early perceptual processes.…”
Section: Discussionsupporting
confidence: 91%
“…This study, consistent with these previous studies, showed that the syllable-rate neural response, although reliably observed in all tested conditions, is modulated by top-down attention. Behaviorally, it has also been shown that a cross-modal sensory stimulus with no linguistic content could interfere with syllabic-level processing (Mattys and Wiget, 2011;Mitterer and Mattys, 2017).…”
Section: Attention Modulation Of Neural Tracking Of the Speech Envelopementioning
confidence: 99%
“…This additional production of a challenging contrast could have increased cognitive load during the perceptual task. Earlier research indicates that cognitive load can reduce perceptual acuity during different kinds of speech discrimination tasks (Mattys et al, 2014;Mattys and Wiget, 2011) and might result in competition for working memory processes at the encoding stage (Mitterer and Mattys, 2017). Based on those findings, the increased task load in the production practice condition in Baese-Berk and Samuel (2016) is likely to result in suboptimal encoding of the trained contrast.…”
Section: Discussionmentioning
confidence: 94%